If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(y+5)=-5y-22
We move all terms to the left:
-8(y+5)-(-5y-22)=0
We multiply parentheses
-8y-(-5y-22)-40=0
We get rid of parentheses
-8y+5y+22-40=0
We add all the numbers together, and all the variables
-3y-18=0
We move all terms containing y to the left, all other terms to the right
-3y=18
y=18/-3
y=-6
| 3y=6;y= | | 8b=4b+4 | | x5-2x4-17x3+34x2+72x-144=0 | | 2=k÷4-1 | | 5x35=10 | | 2x(2)-28=-134 | | -3x+58=125 | | -21d=-462 | | -70=5-3(5x+5) | | 3m-1+4m=-10+8m | | y=1/2+7 | | 2n+9+2n=1 | | 4x+5(3x-2)-4=7x-19 | | 3(x2)=x-18 | | –21d=–462 | | 5x-12(3x+30)=48 | | 8+2h=2h | | (-3x+58)=125 | | 5x-12(3x+30)=40 | | x/2+20=30 | | –8z=–5z+9 | | 2x²−6x+10=0 | | -3/2=-4/3w-8/5 | | D=50c | | 19=-5+2n=6n | | (6x−3)=(4x−7) | | -3x2+10x-3=0 | | 4x+32x-5=70 | | 3x/4-7=-10 | | 0.7xx=5 | | H(t)=t^2÷10+2t | | 6x−3=4x−7 |